Integrasi Knowledge Management System Dan Teknik Knowledge Discovery In Database Dalam Sharing Culture Pada Proses Pembelajaran Berbasis Blended Learning - Iswandi Saputra; Sarjon Defit; Gunadi Widi Nurcahyo (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Education is rapidly changing in the digital age, especially with blended learning, which mixes online and in-person classes. This approach is popular because it offers a well-rounded learning experience. However, getting students and teachers to share knowledge remains a challenge. This study looks at how combining Knowledge Management Systems (KMS) and Knowledge Discovery in Databases (KDD) can help improve knowledge sharing in blended learning at universities. By analyzing data from the E-Learning section of UPI YPTK Padang, involving 120 students, the research aims to create more effective learning systems that encourage sharing. It's a step towards better education in the digital era, promoting collaboration and knowledge exchange among students and educators.